2019
DOI: 10.1016/j.cmi.2018.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged and large outbreak of invasive group A Streptococcus disease within a nursing home: repeated intrafacility transmission of a single strain

Abstract: Inadequate infection control and improper wound-care practices likely led to this 28-month-long outbreak of severe infections in a skilled nursing facility. Whole genome sequencing and phylogenetic analysis suggested that intrafacility transmission of a single highly transmissible GAS strain was responsible for the outbreak in facility A. Integration of genomic epidemiology tools with traditional epidemiology and infection control assessments was helpful in investigation of a facility-wide outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Fifteen studies reported outbreaks caused by bacteria [15-17, 20, 22, 24, 27, 32-39] and 22 studies were outbreaks by viruses [14,18,19,21,23,25,26,[28][29][30][31][40][41][42][43][44][45][46][47][48][49][50]. The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38]. The most affected site was respiratory tract (n = 12) [32, 35, 36, 39-45, 48, 50], followed by gastrointestinal (GI) tract (n = 10) [14,16,23,26,27,31,33,46,47,49].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies reported outbreaks caused by bacteria [15-17, 20, 22, 24, 27, 32-39] and 22 studies were outbreaks by viruses [14,18,19,21,23,25,26,[28][29][30][31][40][41][42][43][44][45][46][47][48][49][50]. The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38]. The most affected site was respiratory tract (n = 12) [32, 35, 36, 39-45, 48, 50], followed by gastrointestinal (GI) tract (n = 10) [14,16,23,26,27,31,33,46,47,49].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
“…Three studies analyzed the data of multiple outbreaks of viral gastroenteritis and influenza-like illness that occurred in multiple facilities for a certain period of time [14,46,48]. The outbreaks in 23 studies affected both the residents and HCWs [14,20,22,23,25,26,29,31,33,[35][36][37][38][39][40][41][43][44][45][46][47][48][49], and the outbreaks of 14 studies affected only the residents [15-19, 21, 24, 27, 28, 30, 32, 34, 42, 50].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
See 3 more Smart Citations